Comparison of the effect of mesh-plug, Lichtenstein, transabdominal preperitoneal, and totally extraperitoneal hernia repair: A network meta-analysis - Shi,Yi-Hua (2020)
SUMMARY OBJECTIVE To compare Mesh-plug, Lichtenstein, transabdominal preperitoneal (TAPP), and totally extraperitoneal (TEP) repairs in regards to operation time, seroma, infection, and recurrence of inguinal hernia repair. METHODS Relevant literature was searched in the Cochrane Library, Pubmed, and Embase. Furthermore, the analysis of randomized controlled studies (RCTs) was performed using methods recommended by the Cochrane Collaboration. The main outcomes including operation time, seroma, infection, and recurrence were evaluated. RESULTS A total of 38 RCTs with 3255 patients were included in the meta-analysis. In addition, the comparison between Mesh-plug, Lichtenstein, TAPP, and TEP showed the differences were not significant regarding operation time, seroma, infection, and recurrence. CONCLUSIONS Meta-analysis suggests that Mesh-plug, Lichtenstein, TAPP, and TEP are comparable in the outcomes of hernia repair, such as operation time, seroma, infection, and recurrence.